Percutaneous Transhepatic Tunneled Dialysis Catheter For Hemodialysis Access Failure - Azad, Pulak; Rizvi, Yasir Sultan; Jha, Lakshmi Kant; Tyagi, Pranav; Rastogi, Vikas (Journal of Clinical Nephrology, 2025)
Vascular access failure is not only a big challenge for nephrologists but also a big threat for patients on haemodialysis. Due to various causes, hemodialysis patients land eventually at this dead end. Patients who have undergone multiple surgeries have intrabdominal adhesions which makes peritoneal dialysis impossible. Such patients have two options; translumbar and transhepatic access. We report a case of a 54-year-old woman who had vascular access failure. She was obese and was apprehensive about the translumbar approach of tunneled catheter placement. The transhepatic tunneled catheter was planned and under ultrasound and fluoroscopy guidance, it was inserted. The patient is undergoing hemodialysis from this access successfully.